Nonstationary INAR(1) Process with th-Order Autocorrelation Innovation - Kaizhi Yu; Hong Zou; Daimin Shi (Abstract and Applied Analysis)
This paper is concerned with an integer-valued random walk process with qth-order autocorrelation. Some limit distributions of sums about the nonstationary process are obtained. The limit distribution of conditional least squares estimators of the autoregressive coefficient in an auxiliary regression process is derived. The performance of the autoregressive coefficient estimators is assessed through the Monte Carlo simulations.